Potential Protection of Coeloglossum viride var. Bracteatum Extract against Oxidative Stress in Rat Cortical Neurons - Guo, Zhe; Pan, Rui-Yuan; Qin, Xiao-Yan (Journal of Analytical Methods in Chemistry, 2013)
The present study explored the neuroprotective effect of Coeloglossum viride var. bracteatum extract (CE) against oxidative stress in rat cortical neurons. The results demonstrated that administration of CE inhibited hydrogen peroxide-induced neurotoxicity tested by MTT, LDH release, and TUNEL assays. We further found that CE inhibited the activation of caspase-3 (Csp3) induced by hydrogen peroxide. Moreover, CE was found to reverse the hydrogen peroxide-induced downregulation of active AKT and Bcl-2. We then showed that the neuroprotective effect of CE was blocked by adding the AKT inhibitor, Ly294002. Thus, our data strongly indicated that CE played a neuroprotective role against oxidative stress-induced neurotoxicity.